Bacterial adherence to human endothelial cells in vitro. - Ogawa, S K (1985)
Differences in the ability of bacteria to adhere to normal valvular endothelium may account for the predominance of particular species as pathogens in acute endocarditis. An in vitro adherence assay was developed to simulate the host surface encountered in acute bacterial endocarditis by using confluent monolayers of human endothelial cells. Adherence of 32 gram-positive and -negative blood culture isolates to this surface was compared. All five Staphylococcus aureus strains tested were highly adherent to endothelial cells, as was one gram-negative strain (Serratia marcescens). The remaining gram-positive and -negative isolates, including four viridans streptococci, were relatively nonadherent. Transmission electron microscopy demonstrated attachment of Staphylococcus aureus and invagination of the underlying endothelial cell membrane at 1 h followed by engulfment of large numbers of bacteria after 3 h. The intracellular bacteria appeared to be contained within vacuoles. Preferential attachment of some strains of bacteria, in particular Staphylococcus aureus, to human endothelial cells occurred in vitro, suggesting that adherence is an important determinant of bacterial pathogenicity in acute endocarditis. Active uptake of bacteria by endothelial cells may help account for the virulence of Staphylococcus aureus in endovascular infections and for the ability of this organism to establish multiple metastatic foci of infection.